Copyright’s Illogical Exclusion of Conceptual Art - Said, Zahr K. (The Columbia Journal of Law & the Arts, 2016)
Many conceptual artists creating art in the contemporary era rebel against staid notions of what art can be, by using found, recycled, nontraditional, or natural materials.1 For example, noted photographer and sculptor Andy Goldsworthy works only with natural materials, typically found outside, and transformed through use of his hands, teeth, and found tools: “His raw material is the natural world. He balances slivers of sandstone, slate, and oak into improbable cairns; painstakingly fuses sycamore leaves and horse-chestnut stalks into filigree shapes; molds humpback sculptures out of sand; and fashions giant snowballs that gently melt to reveal pebbles, pine needles, and twigs.” 2 He writes: “[I] can’t edit the materials I work with. My remit is to work with nature as a whole.” 3 Goldsworthy’s artistic mission, in other words, is to work with materials in the natural world with the understanding that they will decay, or last only ephemerally